Predictive Modeling of Academic Achievement: Combined Effects of Psychological Capital and Self-Handicapping Behaviors Among Form 2 Students in Tswapong Region, Botswana (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
AbstractBackground: Academic underachievement in Botswana's Tswapong Region has persisted despite substantial government investment in education infrastructure and teacher development programs. The region's five-year mean performance declined from 42.70% (2018) to 31.55% (2022), restricting students' access to tertiary education and diminishing their vocational prospects. While previous investigations have examined social and pedagogical factors, the psychological determinants, particularly psychological capital and self-handicapping behaviors, remain inadequately explored within this educational context.Objective: This study examined how psychological capital and self-handicapping independently and collectively predict academic achievement among Form 2 students in Tswapong Region. The investigation further explored gender differences in these psychological constructs and their differential relationships with academic performance.Methods: An exploratory correlational design was employed among 372 Form 2 students (162 males, 210 females) from six purposively selected secondary schools. Data were collected using adapted instruments: the Academic Psychological Capital Questionnaire (APCQ) measuring hope, efficacy, resilience, and optimism; the Academic Self-Handicapping Questionnaire (ASHQ) assessing behavioral and claimed handicapping; and end-of-term summative assessment scores reflecting academic achievement. Standard multiple regression analysis determined the collective predictive capacity of psychological capital and self-handicapping, while bivariate correlations and independent samples t-tests explored individual relationships and gender differences.Results: Psychological capital demonstrated a weak positive correlation with academic achievement (r =.27, p < .001), while self-handicapping showed a moderate negative association (r = -.28, p < .001). Gender analysis revealed no significant differences in psychological capital (t = -1.36, p > .05), though males reported substantially higher self-handicapping behaviors (t = 7.70, p < .001). The regression model was statistically significant, F(2, 369) = 16.19, p < .001, with both predictors collectively explaining 7.6% of achievement variance. Self-handicapping emerged as the stronger predictor (β = -.28, p < .001), while psychological capital's contribution was non-significant (β = .25, p > .05) when considered alongside self-handicapping.Conclusions: Self-handicapping represents a more potent determinant of achievement than psychological capital among Tswapong secondary students. The modest explained variance suggests additional unmeasured factors substantially influence academic performance in this context. Gender-specific patterns in self-handicapping behaviors necessitate differentiated intervention approaches, particularly for male students who demonstrated elevated handicapping tendencies across behavioral and claimed dimensions.